Tantangan dan Strategi Pelayanan Diakonia Karitatif - Zakeus Daeng Lio; Nikolaus Anggal; Maria Ina Kurnia (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2020)
The purpose of the research is to describe the implementation, the challenges, and the strategy of the Diaconia Caritative that has been implement in the social and religious activities, and to analyze the four elements in SWOT Analysis of the implementation of this program in order to discover the new description of strategy of the said program. This research uses the qualitative approach with a descriptive analysis method. The data gathering method that is being used is through field observation, interview and photograph documentation. The result of the research data is program shows the challenges and the strategy to overcome the challenges. The result of the SWOT analysis shows the tendency of formulating two new strategies. The first is the strategy SO and the second strategy is WO.